AB0581 Two years existence of reuma.pt/vasculitis – the portuguese registry of vasculitis. (15th June 2017) - Khmelinskii, N; Ponte, C; Peixoto, D; Rodrigues, M; Teixeira, L; Sousa, S; Aleixo, J; Pedrosa, T; Serra, S; Castelão, W; Cordeiro, A; Cordeiro, I; et al.
Abstract : Background: The vasculitides are a group of relatively rare diseases with different manifestations and outcomes. New therapeutic options have led to the need for long-term registries. The Rheumatic Diseases Portuguese Register, Reuma.pt, is an electronic clinical record, created in 2008, which currently includes specific protocols for 11 diseases and >16000 patients registered from 79 national and international rheumatology centres. Since October 2014, a dedicated protocol to vasculitis has been created as part of the European Vasculitis Society initiative of having compatible European registries. Objectives: To describe the structure of Reuma.pt/Vasculitis and characterize the patients registered over the last two years. Methods: We developed a dedicated web-based software to enable prospective collection and central storage of anonymised data from patients with vasculitis. All Portuguese rheumatology centres were invited to participate. Data regarding demographics, diagnosis, classification criteria, imaging and laboratory tests, outcome measures of prognosis, damage, disease activity and quality of life, and treatment were collected. We performed a cross-sectional descriptive analysis of all patients registered up to January 2017. Results: A total of 492 patients, with 1114 visits, from 11 centres were registered in Reuma.pt/Vasculitis. The mean age was 53±20 years at last visit; 68% were females. The diagnoses followed the 2012 Chapel Hill Consensus nomenclature (Table 1 ). The most common diagnoses were Behçet's disease (BD) (39%) and giant cell arteritis (GCA) (20%). Patients with BD met the International Study Group 1990 criteria, the International Criteria for BD 2006 and 2013 in 84%, 95% and 95% of cases, respectively. Patients with GCA met the 1990 American College of Rheumatology criteria in 95% of cases. Data on vascular ultrasound was available in 74% of patients; 73% compatible with the diagnosis. Assessment of the Birmingham Vasculitis Activity Score (BVAS) and Vasculitis Damage Index (VDI) was available for all vasculitides and the Five Factor Score calculation of survival rate for ANCA associated vasculitis (AAV) and polyarteritis nodosa (PAN). The mean BVAS at first visit was 18±7 for AAV and 15±9 for PAN; the mean VDI at last visit was 3±2 for AAV and 2±2 for PAN. Health related quality of life assessments (SF-36, EQD5, FACIT and HADS) were also collected. Treatment registry with the disease assessment variables shown in graphics was available for all patients; only 6% were under biologic treatment. Conclusions: Reuma.pt/Vasculitis is a registry adapted for routine care, allowing an efficient data repository at a national level with the potential to link with other international databases. It facilitates research, trials recruitment, service planning and benchmarking. Disclosure of Interest: None declared